Urinary Analysis of FGFR3 and TERT Gene Mutations Enhances Performance of Cxbladder Tests and Improves Patient Risk Stratification. Issue 4 (30th April 2023) - Lotan, Yair; Raman, Jay D.; Konety, Badrinath; Daneshmand, Siamak; Schroeck, Florian; Shariat, Shahrokh F.; Black, Peter; de Lange, Michel; Asroff, Scott; Goldfischer, Evan; Efros, Mitchell; Chong, Kian Tai; et al.
Abstract : Purpose: Cxbladder tests are urinary biomarker tests for detection of urothelial carcinoma. We developed enhanced Cxbladder tests that incorporate DNA analysis of 6 single nucleotide polymorphisms for the FGFR3 and TERT genes, in addition to the current 5 mRNA biomarkers and clinical risk factors. Materials and Methods: Two multicenter, prospective studies were undertaken in: (1) U.S. patients with gross hematuria aged ≥18 years and (2) Singaporean patients with gross hematuria or microhematuria aged >21 years. All patients provided a midstream urine sample and underwent cystoscopy. Samples were retrospectively analyzed using enhanced Cxbladder-Triage (risk stratifies patients), enhanced Cxbladder-Detect (risk stratifies patients and detects positive patients), and the combination enhanced Cxbladder-Triage × Cxbladder-Detect. Results: In the pooled cohort (N=804; gross hematuria: n=484, microhematuria: n=320), enhanced Cxbladder-Detect had a sensitivity of 97% (95% CI 89%-100%), specificity of 90% (95% CI 88%-92%), and negative predictive value of 99.7% (95% CI 99%-100%) for detection of urothelial carcinoma. Overall, 83% of patients were enhanced Cxbladder-Detect–negative (ie, needed no further work-up). Of 133 enhanced Cxbladder-Detect–positive patients, 59 had a confirmed tumor, of which 19 were low-grade noninvasive papillary carcinoma or papillary urothelial neoplasm of low malignant potential. In total, 40 tumors were high-grade Ta, T1-T4, Tis, including concomitant carcinoma in situ. Of the 74 patients with normal cystoscopy, 41 were positive by single nucleotide polymorphism analysis. Enhanced Cxbladder-Triage and enhanced Cxbladder-Detect had significantly better specificity than the first-generation Cxbladder tests ( P < .001). Conclusions: This study in ethnically diverse patients with hematuria showed the analytical validity of the enhanced Cxbladder tests.